Penerapan Metode Analytical Hierarchy Process Dalam Pemilihan Tempat Cafe di Kisaran - Azhar, Zulfi; Hutahaean, Jeperson (Forum Kerjasama Pendidikan Tinggi, 2020)
To get information about a cafe in accordance with consumer desires is not easy, sometimes consumers feel confused. This is a problem in providing solutions in choosing the right and best cafe places according to the tastes of consumers in Kisaran City. To provide solutions to problems that arise, a decision support system (DSS) is made using the AHP method to make it easier for users to provide solutions to their problems. The method used is to collect data on filling out forms given to consumers who frequently visit several cafes in Kisaran. The results obtained in the implementation of this study were selected as the criteria for a place with the alternative being Callisto Cafe.